The Role of Oversight of The House of Representatives In Facing Covid-19 Pandemic - Solechan Solechan (Administrative Law and Governance Journal, 2020)
Abstract The emergence of Pandemic COVID 19 in Indonesia that suddenly and significantly increased to make the Indonesian government decided that this pandemic is an emergency disaster set in Presidential Decree No. 12 of 2020. Because of this, the government made a quick move to deal with this problem, especially by the House of Representatives who have important functions in government supervision. The House of Representatives must focus on supervising government policies that have been established or that will be formed and certainly suspend the function of legislation that is not related to the context of handling COVID 19 which has not been able to run effectively and efficiently. In this regard, the Government, especially the House of Representatives, emphasized that it should be able to prioritize supervision in protecting the community to face an emergency disaster.Keywords : Surveillance, government, Pandemic